Green Strategies and Sustainable Performance: Evidence from the Banking Sector - Candy; Thresdianto; Yulfiswandi (Journal Of Management Analytical and Solution (JoMAS), 2026)
Corporate social responsibility (CSR) plays a crucial role in achieving a healthy and sustainable economy while prioritizing environmental considerations. For companies operating in the banking sector, CSR implementation is crucial, as banks play a strategic role in promoting sustainable economic development while simultaneously embracing social responsibility toward society and the environment. These efforts can be strengthened through environmental responsibility, green innovation, and green finance. This study aims to examine the influence of perceived environmental responsibility, green innovation, and green finance on corporate social responsibility and sustainable performance. This study employs a quantitative approach, with questionnaires distributed to 198 banking employees in Batam City. Data were analyzed using SmartPLS to evaluate the outer model and inner model. The results demonstrate that perceived environmental responsibility, green innovation, and green finance have a significant positive effect on corporate social responsibility. Corporate social responsibility also has a significant positive effect on sustainable performance. In addition, corporate social responsibility has a significant mediating role in linking the influence of green innovation and green finance on sustainable performance, but is unable to mediate the influence of perceived environmental responsibility on sustainable performance.